Delft design guide - van Boeijen, Annemiek, ....-; Technische Hogeschool Delft; Daalhuizen, Jaap, ....-; Zijlstra, Jelle, ....-; van der Schoor, Roos, ....- (Amsterdam : BIS Publishers, 2013)
The Delft Design Guide presents an overview of product design approaches and methods used in the Bachelor and Master curriculum at the faculty of Industrial Design Engineering in Delft. Product design at Industrial Design Engineering in Delft is regarded as a systematic and structured activity, purposeful and goal-oriented. Due to its complexity, designing requires a structured and systematic approach, as well as moments of heightened creativity. In this guide you will find some 70 strategies, techniques and methods that are taught in Delft. Some are unique to Delft, but many are more commonly known and widely used. The methods and techniques are each described in a practical one-page text, illustrated for further clarification and enriched with further reading suggestions. The Delft Design Guide serves three goals: / Design students can use it as a reference manual in their design projects, managing their personal development in becoming a designer. / Design tutors can use it as a reference manual to support students in their learning process / Professional designers can use the design guide as a reference manual to support their design processes.
Keywords: Industrial design